Impact of Demographic Changes on Inflation and the Macroeconomy - Jong-Won Yoon; Jinill Kim; Jungjin Lee (KDI Journal of Economic Policy, 2018)
Ongoing demographic changes have brought about a substantial shift in the size and age composition of the population, which are having a significant impact on the global economy. Despite potentially grave consequences, demographic changes usually do not take center stage in many macroeconomic policy discussions or debates. This paper illustrates how demographic variables move over time and analyzes how they influence macroeconomic variables such as economic growth, inflation, savings and investment, and fiscal balances, from an empirical perspective. Based on empirical findings—particularly regarding inflation—we discuss their implications on macroeconomic policies, including monetary policy. We also highlight the need to consider the interactions between population dynamics and macroeconomic variables in macroeconomic policy decisions.
Keywords: J11; E31; E21; 330; Demographic Changes; Population Aging; Inflation; Macroeconomic Impact; Savings and Investment; Monetary Policy; Fiscal Policy